Immune evasion in esophageal squamous cell cancer: From the perspective of tumor microenvironment - Rongyang Li; Bing Huang; Hui Tian; Zhenguo Sun (Frontiers in Oncology, 2023)
Esophageal cancer (EC) is one of the most life-threatening malignancies worldwide. Esophageal squamous cell carcinoma (ESCC) is the dominant subtype, accounting for approximately 90% of new incident EC each year. Although multidisciplinary treatment strategies have advanced rapidly, patients with ESCC are often diagnosed at advanced stage and the long-term prognosis remains unsatisfactory. In recent decades, immunotherapy, such as immune checkpoint inhibitors (ICIs), tumor vaccines, and chimeric antigen receptor T-cell (CAR-T) therapy, has been successfully used in clinical practice as a novel therapy for treating tumors, bringing new hope to ESCC patients. However, only a small fraction of patients achieved clinical benefits due to primary or acquired resistance. Immune evasion plays a pivotal role in the initiation and progression of ESCC. Therefore, a thorough understanding of the mechanisms by which ESCC cells escape from anti-tumor immunity is necessary for a more effective multidisciplinary treatment strategy. It has been widely recognized that immune evasion is closely associated with the crosstalk between tumor cells and the tumor microenvironment (TME). TME is a dynamic complex and comprehensive system including not only cellular components but also non-cellular components, which influence hallmarks and fates of tumor cells from the outside. Novel immunotherapy targeting tumor-favorable TME represents a promising strategy to achieve better therapeutic responses for patients with ESCC. In this review, we provide an overview of immune evasion in ESCC, mainly focusing on the molecular mechanisms that underlie the role of TME in immune evasion of ESCC. In addition, we also discuss the challenges and opportunities of precision therapy for ESCC by targeting TME.